North American Women Poets in the 21st Century : Beyond Lyric and Language - Ali, Kazim, 1971-; Sewell, Lisa, 1960- (Book collections on Project MUSE., 2020)
"North American Women Poets in the 21st Century is a wide-ranging collection of the work of 21st-century North American women poets that puts work alongside statements from the poets and essays about their work"--